2017
DOI: 10.1093/cercor/bhx216
|View full text |Cite
|
Sign up to set email alerts
|

Theories of Person Perception Predict Patterns of Neural Activity During Mentalizing

Abstract: Social life requires making inferences about other people. What information do perceivers spontaneously draw upon to make such inferences? Here, we test 4 major theories of person perception, and 1 synthetic theory that combines their features, to determine whether the dimensions of such theories can serve as bases for describing patterns of neural activity during mentalizing. While undergoing functional magnetic resonance imaging, participants made social judgments about well-known public figures. Patterns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 34 publications
5
69
0
Order By: Relevance
“…With respect to these dimensions, the results may provide a parsimonious explanation for cases in which their correlations may cease to be independent and shift. In one example, trait impressions of less familiar others may be more intercorrelated and lower dimensional than those of familiar others (29,30). It may be the case that perceivers rely more on their conceptual trait space, in which trait judgments are highly correlated, to make impressions of unfamiliar others when more specific person knowledge is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to these dimensions, the results may provide a parsimonious explanation for cases in which their correlations may cease to be independent and shift. In one example, trait impressions of less familiar others may be more intercorrelated and lower dimensional than those of familiar others (29,30). It may be the case that perceivers rely more on their conceptual trait space, in which trait judgments are highly correlated, to make impressions of unfamiliar others when more specific person knowledge is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Although the general findings of this study are in line with the previous MVP classification‐based approaches in that they demonstrate that the MPFC represents aspects of familiar identity, the fact remains that the specific type of person information that is being encoded in this region remains elusive. A second study by Thornton and Mitchell () again examined how different models of person perception might relate to the neural representations of others, this time extending the set of identities to 60 well‐known public figures and, instead of a mental simulation task, participants were asked to make inferences as to the personal preferences of each identity (i.e., liked debating with others, see Mitchell et al, 2006). The authors first identified regions that demonstrated reliable identity‐specific patterns of activity by correlating voxel‐wise and pattern‐wise similarities across split halves of the data (Figure c).…”
Section: Decoding the Neural Representation Of Person Knowledgementioning
confidence: 99%
“…Accordingly, dominance and trustworthiness are positively correlated when judging close and admired others [e.g., 7] but negatively correlated when judging unfamiliar and outgroup others [e.g., 2]. Recent work further suggests that close as opposed to distant others may be represented in higher-dimensional spaces more generally, perhaps due to more complex representations of familiar personalities [8]. Together, these recent findings suggest top-down social cognitive factors may shift the dimensional space underlying face-based trait perception and thus how individuals' faces are evaluated within it.…”
mentioning
confidence: 99%